An examination of the relationship between patient satisfaction with healthcare and quality of life in a geriatric population with cancer in the Southeastern United States. Issue 5 (September 2019) - Azuero, Andres; Williams, Courtney P.; Pisu, Maria; Ingram, Stacey A.; Kenzik, Kelly M.; Williams, Grant R.; Rocque, Gabrielle B.
Abstract: Background: Understanding factors that impact patient satisfaction with cancer care within the growing population of older adults living with cancer will contribute to tailoring programs that address patient needs and expectations. Further, patient satisfaction is a determinant of healthcare organizations' institutional performance. The purpose of this study was to investigate the relationship between patient satisfaction with care and health-related quality of life (HRQoL) among Medicare recipients with common cancers types (breast, prostate, or lung cancer). Methods: Cross-sectional analysis of survey data from 637 Medicare beneficiaries (≥65 years) with breast (n = 304), lung (n = 158), or prostate cancer (n = 175) in twelve hospitals in the Southeastern United States. Participants responded eighteen satisfaction questions across five domains. HRQoL was measured with the Physical Component Summary (PCS) and Mental Component Summary (MCS) scores of the SF-12.v2 instrument. Results: SF-12 scores were positively associated with satisfaction domain scores. The magnitude of these associations was small with covariate-adjusted effect sizes r ranging from 0.05 to 0.12. Satisfaction scores were highest within the Quality of Care domain and lowest within the Patient Engagement domain. Conclusions: Patient satisfaction domains had only modest association with HRQoL, indicating that these constructs should not be assumed to correlate. Satisfaction domains, including how patients access care, coordinate care, and engage within the healthcare system, were identified as potential areas for improvement. Patient satisfaction assessment across age groups may inform oncology care providers on ways in which their patients perceive the quality of care received, which ultimately affect healthcare organizations' accreditation, ranking, and reimbursement.